THE DISTRIBUTION OF AVERAGE MOBILE NETWORK SPEEDS IN INDONESIA BASED ON OOKLA DATA - Patrick Welay; Caroline Herfisia Parlina; Ivena Julia Armelinda; Jadiaman Parhusip (Informatika: Jurnal Teknik Informatika dan Multimedia, 2024)
The speed of mobile networks is a key factor in determining the quality of service provided by operators in Indonesia. This study aims to analyze the distribution of average mobile network speeds in Indonesia, based on data obtained from Speedtest by Ookla. The method employed in this research is descriptive statistical analysis to calculate the average download speed, upload speed, and latency across various network providers, namely Telkomsel, XL, IM3 Ooredoo, and Smartfren. The results indicate that Telkomsel achieved the highest download speed with an average of 42.33 Mbps, followed by other providers. Additionally, there is significant variation in internet speeds across regions, with South Jakarta exhibiting higher speeds compared to other areas. This study provides an overview of mobile network performance, which can serve as a reference for users and service providers to improve network quality in the future.